Magnetic resonance imaging as a tool to assess reliability in simulating hemodynamics in cerebral aneurysms with a dedicated computational fluid dynamics prototype: preliminary results - Karmonik, Christof; Zhang, Y. Jonathan.; Diaz, Orlando; Klucznik, Richard; Partovi, Sasan; Grossman, Robert G.; Britz, Gavin W. (Cardiovascular Diagnosis and Therapy, 2014)
Purpose: As an example of enhancing information in clinical image data by computational methods, simulating hemodynamics in cerebral aneurysms by means of computational fluid dynamics (CFD) is currently a topic of active research. Challenges consist in translating this engineering technology into clinical research, validating the simulations and addressing a potential clinical value of the results. In this preliminary study, we demonstrate the use of phase contrast magnetic resonance imaging (pcMRI) for assessing the reliability of CFD results. Materials and methods: For six cerebral aneurysms where intra-aneurysmal velocity information was available by 2D pcMRI, steady CFD simulations with constant inflow were performed using a dedicated CFD prototype system. Major features of the velocity patterns derived from pcMRI were compared to those obtained with the CFD. Results: Good qualitative agreement between measured (2D pcMRI) and simulated (CFD) features of the intra-aneurysmal velocity patterns were obtained. These findings are discussed in the broader framework of the expectations towards CFD simulations in a clinical research setting. Conclusions: Computational simulations reproduce major features of measured velocity patterns in cerebral aneurysms. Looking forward, these simulations need to be refined towards specific applications in clinical research.